Anatomy and Histology of the Male Reproductive System and Sperm Morphology of Leptoglossus Zonatus (Dallas, 1852) (Heteroptera: Coreidae) - Paulo, Mauricio da Silva (2023)
Coreidae is a diverse family formed predominantly by plant-sucking bugs, containing about 520 genera, more or less 3,100 species worldwide, and 165 genera in the Neotropical region. The genus Leptoglossus usually undergoes five instars throughout its life and has a worldwide distribution, especially in the Americas. Leptoglossus zonatus is a phytophagous bug that feeds on Poaceae, Leguminosae, Rutaceae and Punicaceae crops, with maize being its primary food source. Data related to aspects of the reproductive system of Heteroptera are essential to understand the biology of most of its representatives, in addition to assisting in the systematics. Thus, the data from this study could provide helpful information for taxonomy and for understanding the relationships of this species, or genus, with other group members. So, we described the morphology of the male reproductive system and spermatozoa of the bedbug L. zonatus. Adult individuals were collected in Viçosa, MG – Brazil and their reproductive systems were processed for light histology. For morphometry of the spermatozoa, these were collected from the seminal vesicles of males, and the Giemsa dye was used to measure the total length and the DAPI dye to measure the nucleus. L. zonatus has a pair of testes and two distinct types of coiled accessory glands. Each testis has a pecten-shaped, like Machtima crucigera and Coreus marginatus and is surrounded by a red-pigmented, highly tracheolated testicular sheath, as seen in other Coreidae. It has seven elongated follicles joined by testicular sheath septa. The cysts are spherical initially and elongate toward the final phase of spermatogenesis, with an average of 850 spermatozoa per cyst (nine cycles of cell division). Spermatogenesis occurs throughout the adult life of this insect, producing sperm thin and elongated that measures an average of 310 µm in length, with a 36 µm nucleus. They are do not form bundles in the seminal vesicles, being transferred to the female freely during copulation. Characteristics such as the number of follicles per testis and sperm production throughout adult life certainly reflect the reproductive success of L. zonatus, and these findings, including sperm morphometry, may help in future research to understand the diversity, taxonomy, and systematics of the genus Leptoglossus, as well as of other Coreidae in the suborder Heteroptera. Keywords: Hemiptera. Pentatomomorpha. Testicular morphology. Sperm development. Accessory glands.